2011
DOI: 10.1037/a0021379
|View full text |Cite
|
Sign up to set email alerts
|

The impact of school-based mentoring on youths with different relational profiles.

Abstract: Associations between youths' relationship profiles and mentoring outcomes were explored in the context of a national, randomized study of 1,139 youths (54% female) in geographically diverse Big Brothers Big Sisters school-based mentoring programs. The sample included youths in Grades 4 -9 from diverse racial and ethnic backgrounds, the majority of whom were receiving free or reduced-price lunch. Latent profile analysis, a person-oriented approach, was used to identify 3 distinct relational profiles. Mentoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 70 publications
2
81
0
Order By: Relevance
“…This approach is aimed at identifying patterns within an individual's responses, and considers multiple characteristics simultaneously (Laursen et al 2006;Von Eye and Bogat 2006). It was recently used in the field of developmental psychology (Mayseless and Scharf 2009;Schwartz et al 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is aimed at identifying patterns within an individual's responses, and considers multiple characteristics simultaneously (Laursen et al 2006;Von Eye and Bogat 2006). It was recently used in the field of developmental psychology (Mayseless and Scharf 2009;Schwartz et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…A score of 1 represented low self-perception, and 4 represented the high continuum. This measure has been widely used and shows good psychometric qualities (e.g., Schwartz et al 2011;Shapiro et al 2005). …”
Section: Methodsmentioning
confidence: 99%
“…1 (n = 82) 2 (n = 75) 3 (n = 61) 4 (n = 91) academic performance than their peers (Schwartz et al, 2011). For mentees who showed no change or a decrease in PCL during the mentoring program, SBM may have been perceived as a simple extension of teaching; something which, ultimately, failed to improve academic results.…”
Section: Discussionmentioning
confidence: 89%
“…Some meta-analyses found that SBM impact ranged from un-existent (Wood & Mayo-Wilson, 2012) to modest, but significant (DuBois et al, 2011). There is accumulated evidence that SBM effectiveness is influenced by a wide array of factors such as: the mentees' gender (Darling, Bogat, Cavell, Murphy, & Sanchez, 2006) or level of relational risk (Schwartz, Rhodes, Chan, & Herrera, 2011); the mentor's profile, including his/her background in caring and educational roles (DuBois et al, 2011); or the specific implementation of the SBM program (DuBois et al, 2011), such as the existence of appropriate activities (Karcher, 2008) or the duration of SBM relationships (Grossman, Chan, Schwartz, & Rhodes, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…One large randomized study in Latino children did observe different mentoring outcomes by gender and age [8]. Another study found that SBM had differential effects depending on the mentees' relational profile [22]. To further understand what defines successful mentoring relationships among urban Latino children, qualitative research to expand the currently accepted definitions of mentoring relationship quality and its impact would be helpful.…”
Section: Discussionmentioning
confidence: 99%